Importance of early physical rehabilitation in recovery of pain and tactile sensitivity of women with postmastectomy syndrome - Одинець, Тетяна Євгенівна; Манжура, Наталія Анатоліївна (Slobozhanskyi Herald of Science and Sport, 2016)
Odinets T., Manzhura N. Purpose: to determine the expediency of early application of physical rehabilitation to improve the pain and tactile sensitivity of women with postmastectomy syndrome. Material & Methods: theoretical analysis of scientific and methodical literature, analysis of heart rate variability, methods of mathematical statistics. The study involved 135 women with postmastectomy syndrome who underwent radical mastectomy by Madden. Results: at the end of the annual research it was found that women of MG showed significantly better indicators of pain sensitivity in the areas of armpit, deltoid, triceps and forearms; tactile sensitivity – only by armpit compared to MG1. Conclusions: identified the feasibility of early rehabilitation intervention to improve the pain and tactile sensitivity in women during the year training by the first personality-oriented rehabilitation program.